Developing Digital Competence Among Educators in Rural India - Karan Singh; Meera Gupta; Ananya Rao (Journal Emerging Technologies in Education, 2025)
Background. Digital competence has become a fundamental requirement for educators navigating 21st-century learning environments. In rural India, where infrastructural limitations and socio-economic disparities persist, equipping teachers with digital skills is critical to reducing educational inequities and fostering inclusive development. Purpose. This study explores initiatives aimed at developing digital competence among educators in rural Indian contexts, focusing on both the opportunities and systemic challenges involved. The research aims to assess the effectiveness of targeted training programs, identify contextual barriers, and evaluate the sustainability of digital integration in teaching practices. Method. A mixed-methods approach was employed, combining surveys of 150 rural teachers across three Indian states with in-depth interviews and field observations. Results indicate that while most educators demonstrated enthusiasm for technology adoption Results. Results indicate that while most educators demonstrated enthusiasm for technology adoption, significant gaps remain in technical proficiency, access to reliable internet, and availability of culturally relevant digital content. Teachers who received structured, context-specific training exhibited improved confidence, pedagogical innovation, and student engagement. Conclusion. The study concludes that sustained progress in rural digital education requires investment in infrastructure, localized content development, and continuous professional development. These findings contribute to the discourse on digital equity and educational transformation in underserved regions.